Angiosarcoma associated with a Kasabach–Merritt syndrome: report of two cases treated with paclitaxel. (September 2013) - Grellety, Thomas; Italiano, Antoine
Angiosarcomas are rare, aggressive vascular malignancies of endothelial cell differentiation. Kasabach–Merritt syndrome is a rare condition defined by the association of thrombocytopenia and consumption coagulopathy with specific vascular tumors, such as tufted angioma or kaposiform hemangioendothelioma. We report here two cases of angiosarcomas complicated by a Kasabach–Merritt syndrome and their outcome after treatment with paclitaxel.